The new avant-garde in Italy : theoretical debate and poetic practices - Picchione, John, 1949- (Toronto Italian studies., 2004)
This study suggests that some of the contentious views proposed by the neoavanguardia anticipated a wide range of issues that continue to be significant and pressing to this day.